Effect of displacement vector in the direction of arrival estimation / Nor Syaliza Talha - Talha, Nor Syaliza (2007)
There is a relationship between the direction of a signal and the associated received steering vector. Therefore, it should be possible to invert the relationship and estimate the direction of a signal from the received signals. An antenna array should be able to provide for direction of arrival (DOA) estimation. There is also Fourier relationship between the beam pattern and the excitation at the array. This allows the DOA estimation problem to be" treated as equivalent to spectral estimation. This paper clarifies the effect of variation displacement vector in estimating the DOA in a smart antenna application. The objective is to find the optimum value of element spacing where it will give the best DOA estimation of signal impinging on a uniform linear array (ULA). The algorithms used in detecting the DOA are the Multiple Signal Classification (MUSIC) and Estimation of Signal Parameters via Rotational invariance Techniques (ESPRIT). The two algorithms produce an ambiguity in the estimated direction-of-arrival results, when the antenna element spacing on a linear array is more than half a wavelength.